Anticancer, antioxidant potential and profiling of polyphenolic compounds of Wrightia tinctoria Roxb. (R.Br.) bark - Nishat Fatima; Mohammad Kaleem Ahmad; Jamal Akhtar Ansari; Zulfiqar Ali; Abdul Rahman Khan; Abbas Ali Mahdi (Wolters Kluwer Medknow Publications, 2016)
Wrightia tinctoria Roxb. (R.Br.) is an Ayurvedic remedy, ethnomedically used in the treatment of various ailments. The present work was carried out to evaluate the anticancer and antioxidant activity as well as total phenolic and phytochemical contents of W. tinctoria bark methanolic extract (WTBM) by high-performance liquid chromatography (HPLC)-diode array detector. Antiproliferative activity of WTBM was evaluated against MDA-MB-231 and MCF-7 cancer cells by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, colony formation, and Hoechst staining. In addition, the antioxidant potential was determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and 2,2- azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical cation decolorization assay. Total phenolic content was assessed by Folin-Ciocalteu method. The results demonstrated that WTBM exhibited significant antiproliferative effect against MDA-MB-231 (IC 50 = 88.9 ± 1.27 μg/ml) and MCF-7 (IC 50 = 45.71 ± 7.74 μg/ml) cancer cells in time- and dose-dependent manner. WTBM significantly suppresses colony formation and induces apoptosis in both MDA-MB-231 and MCF-7 cells as evident by morphological assessment, clonogenic assay, and Hoechst staining. The total phenolic content of WTBM was found to be 30.3 gallic acid equivalent mg/g dry weight of bark extract while IC 50 value for DPPH and ABTS radical scavenging activity was 72.2 ± 2.8 μg/ml and 45.16 ± 1.95 μg/ml, respectively. HPLC analysis showed the presence of gallic acid, rutin, and quercetin in WTBM. These findings demonstrated that WTBM significantly inhibited proliferation of breast cancer cells and induced apoptosis, suggesting the potential chemopreventive activity of W. tinctoria bark.